The lion, the witch and the wardrobe - Lewis, C. S.; Baynes, Pauline (Collins London, 1976)
A new edition of this famous and incredibly popular book. This is the best-loved of all the Chronicles of Narnia, the first one ever written, the one that everyone remembers reading.